THE INFLUENCE OF TEACHER ASSESSMENT ON TOURISM VOCATIONAL STUDENTS READINESS FOR ENTERING INDUSTRY - Fitri Yasih; Siti Isma Sari Lubis; Violintikha Harmawan; Nurul Inayah Hutasuhut (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
Reliable human resources, with strong national development potential, are students who graduated from Vocational Schools. Indirectly, SMK graduates make a positive contribution in the industrial world. The national development in question must be able to meet the demands for quality and relevance to the world of work in his time so that vocational students have a competitive advantage and can survive in the face of national global competition in the current industrial era 5.0. This research focuses on reviewing various literature regarding the continuing professional development of vocational teachers. The research was conducted in June 2019 at SMK N 1 Tourism, Kab. Siak, Riau Province. The sample in this study was carried out using a purposive random sampling technique. Determining the sample of respondents in this study, namely teachers (main data source) as research subjects, all subject teachers at SMK N 1 Tourism were selected. The results obtained in this study, namely a review of the literature review on continuing professional development for vocational teachers, can be formulated five dimensions which become the theoretical structure of teacher continuing professional development tools, namely: (1) learning development and assessment, (2) education and training according to the field, (3) carry out scientific publications, (4) have innovative work publications, (5) carry out reflections, and collaborations.Keywords: Assessment, Teachers, SMK